Integrating information from semi-structured interviews into management strategy evaluation: A case study for Southeast United States marine fisheries - Damiano, Matthew; Wager, Bethany; Rocco, Alex; Shertzer, Kyle W.; Murray, Grant D.; Cao, Jie (Frontiers in Marine Science, 2022)
Management strategy evaluation (MSE) has become a more common tool for engaging stakeholders in fisheries management, and stakeholder participation in MSE is increasingly recognized as a vital component of the process. The participation of stakeholders, specifically fishers, in MSE is of particular importance because they often possess intimate knowledge of the socio-ecological management system that MSE seeks to model. When the resources to conduct a “full” MSE with direct fisher involvement are unavailable, MSEs are sometimes conducted by desk-based analysts with no fisher engagement. We propose an intermediate framework in which information collected from semi-structured interviews is used to inform a “desk-based” MSE. We demonstrate that semi-structured interviews with commercial and recreational fishers can elicit some of the same kinds of information that fishers provide during direct participation in MSE. We conducted 30 semi-structured interviews with commercial and recreational fishers from the Southeast United States participating in either Atlantic cobia (Rachycentron canadum) or black sea bass (Centropristis striata) fisheries. We collected primarily qualitative and some quantitative information about preferred conceptual objectives and management measures, and how their fishing behavior has changed in response to past management action. Commercial fishers generally preferred conceptual objectives and management measures that align with traditional MSY-based fisheries management, while recreational fishers’ responses were substantially more heterogeneous, indicating a more diverse range of desired objectives and preferred management measures. We synthesized this information to develop a suite of management procedures that employ a range of fishing mortality-based constant-catch harvest control rules and size-based management measures for simulation testing against preferred objectives by sector. We demonstrate that integrating information from semi-structured interviews with MSE in this way offers a cost-effective alternative intermediate approach to fisher participation in MSE when direct participation is not possible.